PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PBL) UNTUK MENINGKATKAN KEAKTIFAN PESERTA DIDIK KELAS X MA DARUL KHAIRAAT TAFAMUTU KOTA TERNATE PADA PELAJARAN GEOGRAFI - Samili, Asnita Ode; Adjam, Syarifuddin; Hasim, Jainudin; Muhammad, Mina H. (Jurnal GeoCivic, 2025)
This study aims to determine the application of the Project Based Learning (PBL) learning model in increasing the activeness of class X students of MA Darul Khairaat Tafamutu, Ternate City in Geography subjects. Student activeness during the learning process is an important factor that influences the success of learning, but so far the activeness of students in class X is still relatively low. The PBL model was chosen as an innovative solution because it places students as the center of learning through active involvement in projects relevant to Geography material. This study uses the classroom action research (CAR) method which is implemented in several cycles. Data were collected through observations of student activeness, interviews, motivation questionnaires, documentation, and assessment of learning outcomes. Data analysis was carried out qualitatively and quantitatively to measure the increase in student activeness and response to the application of PBL. The results of the study showed that the application of the Project Based Learning learning model significantly increased student activeness in the Geography learning process. Students became more enthusiastic, actively asked questions, discussed, and collaborated in completing projects. In addition, learning motivation and understanding of Geography concepts also increased. Obstacles encountered during implementation can be overcome by improvements in each learning cycle.